Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3892/etm.2021.10627
|View full text |Cite
|
Sign up to set email alerts
|

The use of polypropylene mesh in inguinal hernia surgery: A retrospective study

Abstract: Previously, inguinal hernia surgery was based exclusively on repairing the abdominal wall defects using the patient's own tissues, which were put in contact with and tensioned to recalibrate the natural orifices. At present, inguinal hernia surgery is based almost solely on mounting an allograft, which has the role of strengthening the weakened groin region that allowed the herniation. This modern method of operation on inguinal hernia can be performed in a classic or laparoscopic manner. The mesh is made of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…It has a pronounced therapeutic effect on inguinal hernia patients and puts forward higher requirements for nursing. In addition, it is worth noting that surgery is a traumatic stress response, and postoperative pain is an inevitable, normal physiological response, which will cause patients to have physiological and psychological abnormal reactions, which may affect the curative effect of surgery [ 17 ]. Therefore, in addition to the effective surgical treatment of inguinal hernia patients, we should comprehensively consider patients' physical and mental symptoms and implement targeted nursing interventions, to provide more references for improving the overall surgical efficacy and quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a pronounced therapeutic effect on inguinal hernia patients and puts forward higher requirements for nursing. In addition, it is worth noting that surgery is a traumatic stress response, and postoperative pain is an inevitable, normal physiological response, which will cause patients to have physiological and psychological abnormal reactions, which may affect the curative effect of surgery [ 17 ]. Therefore, in addition to the effective surgical treatment of inguinal hernia patients, we should comprehensively consider patients' physical and mental symptoms and implement targeted nursing interventions, to provide more references for improving the overall surgical efficacy and quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine curative effect of surgery [17]. erefore, in addition to the effective surgical treatment of inguinal hernia patients, we should comprehensively consider patients' physical and mental symptoms and implement targeted nursing interventions, to provide more references for improving the overall surgical efficacy and quality of life of patients.…”
Section: Specific Operationmentioning
confidence: 99%
“…The research of Eickhoff et al demonstrated how textile modifications of suture strands—in particular, the surface structures of sub-macrophage-sized patterns—led to an improved foreign body reaction [ 13 ]. The enlarged surface area of polymer filaments consisting of filaments larger than macrophages induces and increases foreign body reactions, even for biomaterials that are considered to be of good biocompatibility, such as PP [ 16 ]. Our results further illuminate this ostensible contradiction: UFPET meshes led to decreased scar induction in biocompatibility assessments, as indicated by the reduced IFBG and OFBG after 7 days and the smaller IFBG after 21 days but especially evidenced by the significant reduction in the OFBG compared to all other tested meshes after 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…6 The biomedical materials industry has made significant strides in research and development, which has resulted in manufacturing surgical meshes that are largely non-reactive and biocompatible. 7,8 When surgical meshes are implanted in the human body, various responses can be triggered, including inflammation, fibrosis, calcification, thrombosis, and infection. This has been observed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%